Mekanisme Penyusunan Peraturan Daerah Pendidikan oleh DPRD Kabupaten Pesisir Selatan - Muhamad Abdul Aziz (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to analyze the mechanism for drafting the Regional Regulation (Perda) on Education by the Regional House of Representatives (DPRD) of Pesisir Selatan Regency, focusing on legislative stages, key actors, and both normative and practical challenges encountered. Perda serves as a vital instrument for implementing regional autonomy and improving the quality of local education. Using a descriptive-qualitative approach, data were collected through observation, interviews, and literature review. The findings reveal that although formal legislative stages such as inclusion in the Regional Legislative Program (Prolegda), academic drafting, deliberation, and ratification have been followed, their effectiveness remains limited. Normative barriers include regulatory overlaps and weak academic foundations. Practical obstacles involve limited technical capacity among DPRD members, bureaucratic dominance, and lack of meaningful public participation. Additionally, evaluation and implementation processes are not yet responsive to the dynamic needs of coastal education. Therefore, institutional capacity-building and the adoption of participatory, data-driven legislative approaches are crucial to improving the quality of the Education Regulation in Pesisir Selatan.